PENGARUH LABA BERSIH DAN ARUS KAS OPERASIONAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN INDEX IDX 30 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015-2017 - ATIKA RAHMI; LILI FADLI MUHAMMAD; MIA SYOFRINA (Institut Bisnis Muhammadiyah Bekasi, 2021)
The purpose of this research is to analyze how much the factor of net income and operating cash flow on dividend policy is proxied by dividend payout ratio on IDX Index 30 companies listed on the Indonesia Stock Exchange (IDX). The variables examined in this study are Net Income ( ) and Operating Cash Flow ( ) as the independent variable and Dividend Policy (Y) as the dependent variable. The sampling technique used was the purposive sampling method where the sample used in this study was 18 IDX Index 30 companies listed on the Indonesia Stock Exchange for 3 years, namely from 2015 to 2017. The analysis technique used in this study used analysis classic assumption test, multiple linear regression analysis, hypothesis test analysis and coefficient of determination analysis.